A host-range restricted parainfluenza virus type 3 (PIV3) expressing the human metapneumovirus (hMPV) fusion protein elicits protective immunity in African green monkeys - Tang, Roderick S.; Mahmood, Kutubuddin; MacPhail, Mia; Guzzetta, Jeanne M.; Haller, Aurelia A.; Liu, Hui; Kaur, Jasmine; Lawlor, Heather A.; Stillman, Elizabeth A.; Schickli, Jeanne H.; Fouchier, Ron A.M.; Osterhaus, Albert D.M.E.; et al. (Vaccine, 2005)
Human metapneumovirus (hMPV) infection causes respiratory tract disease similar to that observed during human respiratory syncytial virus infection (hRSV). hMPV infections have been reported across the entire age spectrum although the most severe disease occurs in young children. No vaccines, chemotherapeutics or antibodies are presently available for preventing or treating hMPV infections. In this study, a bovine/human chimeric parainfluenza virus type 3 (b/h PIV3) expressing the human parainfluenza type 3 (hPIV3) fusion (F) and hemagglutinin-neuraminidase (HN) proteins was engineered to express hMPV fusion (F) protein from the second genome position (b/h PIV3/hMPV F2) with the goal of generating a novel hMPV vaccine. b/h PIV3/hMPV F2 was previously shown to protect hamsters from challenge with wt hMPV (Tang RS, Schickli JH, Macphail M, Fernandes F, Bicha L, Spaete J, et al. Effects of human metapneumovirus and respiratory syncytial virus antigen insertion in two 3’ proximal genome positions of bovine/human parainfluenza virus type 3 on virus replication and immunogenicity. J Virol 2003;77:10819–28) and is here further evaluated for efficacy and immunogenicity in African green monkeys (AGMs). AGMs immunized intranasally and intratracheally with b/h PIV3/hMPV F2 generated hMPV- and hPIV3-specific humoral and cellular immune responses and were protected from wt hMPV infection. In a separate study, the host-range restriction of b/h PIV3/hMPV F2 replication relative to wt hPIV3 was performed in rhesus monkeys to demonstrate attenuation. These studies showed that b/h PIV3/hMPV F2 was immunogenic, protective and attenuated in non-human primates and warrants further evaluation in humans as a vaccine candidate for prevention of hMPV-associated respiratory tract diseases.